The Relationship Between Online Game Addiction and Cognitive Function Among Students in the E-Sport Student Activity Unit at Jambi University - Anggun Meiliani Aulia; Riska Amalya Nasution; Yulia Indah Permata Sari (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2025)
Excessive online gaming negatively impacts individuals, especially in academic settings, by reducing motivation, commitment, and cognitive functions critical for success. This study explores the correlation between online game addiction and cognitive function among members of the E-Sports Student Activity Unit at Universitas Jambi. A quantitative correlational design was applied with 66 participants selected by proportionate stratified random sampling. Online game addiction and cognitive function were assessed using the GASA and MoCA-Ina instruments, respectively. Results showed that 37.9% of respondents had moderate addiction levels, while 65.2% maintained normal cognitive function. Spearman rho test revealed a significant negative correlation (r = 0.784, p < 0.05), indicating that higher addiction levels were associated with lower cognitive function. The findings suggest the need for educational and counseling interventions to promote balanced gaming and academic performance.